Factors Influencing Sustainability of Women Entrepreneurship in Oman: Challenges and Opportunities - Ibrahim, Omer Ali; Alqassabi, Mohammed Ali; Abdel-Gadir, Sufian Eltayeb Mohamed (Journal of Ecohumanism, 2024)
This paper aims to identify the key factors influencing sustainability of women entrepreneurship in Oman. The study adopted a mixed design approach. The data for the study was collected through a structured questionnaire including 107 women entrepreneurs, in addition to interviews with two women entrepreneurs in Muscat A stratified random sampling was employed to provide a better representation of the women entrepreneurs sectors. Exploratory factor analysis (EFA) and T-test and Chi-square test were used to determine the key factors influencing the sustainability of women entrepreneurship in Oman and validate the study hypotheses. The main findings of the study showed that entrepreneurial characteristics, entrepreneurial personalities, government support, external environment, and entrepreneurial human capital have a significant impact on sustainability of women entrepreneurship in Oman. Furthermore, 86.2% of women entrepreneurs in Oman were experiencing loses during the last four years. The main challenges facing women entrepreneurship in Oman include complexity of rules and regulations of doing business, unfair competitions with large enterprises, lack of access to finance, and lack of skilled workers. The implications of such challenges have been discussed and some recommendations to promote sustainability of women entrepreneurship in Oman have been suggested.